Green narratives or greenwashing? An ecological discourse analysis of IKN-related discourses - Rahayu, Famala Eka Sanhadi; Hasyim, Muhammad; Arifin, Muhammad Bahri (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to determine whether the IKN-related discourses produced by the Indonesian government constitute a green narrative that promotes ecological conservation and protection or are merely greenwashing strategies designed to gain public acceptance. Fifty-two articles taken from the Indonesian government’s official website about IKN, https://ikn.go.id/ are the data source of this research. Utilizing AntConc and NVivo software, the researchers investigate the word frequency of environmentally related lexical choices and complete an analysis of the six-taxonomy of greenwashing. The results reveal that five greenwashing strategies are prominent: attention deflection, deceptive manipulation, decoupling, selective disclosure, and inefficient public voluntary programs. These strategies reflect the gap between environmental claims and actions, with the government focusing on technological solutions while downplaying or omitting critical ecological issues such as deforestation, biodiversity loss, and indigenous displacement. This research makes a valuable contribution to the field of ecolinguistics by emphasizing the need for a critical examination of governmental environmental narratives, particularly in situations where ecological claims are used to justify large-scale development. This analysis could be further developed in the future by integrating indigenous perspectives, ecological data, and longitudinal monitoring of IKN's environmental impact.